Defective Natriuretic Peptide Receptor Signaling in Skeletal Muscle Links Obesity to Type 2 Diabetes - Coué, Marine; Badin, Pierre-Marie; Vila, Isabelle K.; Laurens, Claire; Louche, Katie; Marquès, Marie-Adeline; Bourlier, Virginie; Mouisel, Etienne; Tavernier, Geneviève; Rustan, Arild C.; Galgani, Jose E.; Joanisse, Denis R.; et al. (Diabetes (New York, N.Y.), 2015)
Circulating natriuretic peptide (NP) levels are reduced in obesity and predict the risk of type 2 diabetes (T2D). Since skeletal muscle was recently shown as a key target tissue of NP, we aimed to investigate muscle NP receptor (NPR) expression in the context of obesity and T2D. Muscle NPRA correlated positively with whole-body insulin sensitivity in humans and was strikingly downregulated in obese subjects and recovered in response to diet-induced weight loss. In addition, muscle NP clearance receptor (NPRC) increased in individuals with impaired glucose tolerance and T2D. Similar results were found in obese diabetic mice. Although no acute effect of brain NP (BNP) on insulin sensitivity was observed in lean mice, chronic BNP infusion improved blood glucose control and insulin sensitivity in skeletal muscle of obese and diabetic mice. This occurred in parallel with a reduced lipotoxic pressure in skeletal muscle due to an upregulation of lipid oxidative capacity. In addition, chronic NP treatment in human primary myotubes increased lipid oxidation in a PGC1α-dependent manner and reduced palmitate-induced lipotoxicity. Collectively, our data show that activation of NPRA signaling in skeletal muscle is important for the maintenance of long-term insulin sensitivity and has the potential to treat obesity-related metabolic disorders.